2022
DOI: 10.3390/biochem2010005
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Mass Spectrometry Approach to Study SARS-CoV-2 Proteins in Human Plasma and Saliva Proteome

Abstract: Since the start of the COVID-19 outbreak, more than four million people have died of this disease. Given its ability to provide a precise response, mass spectrometry-based proteomics could represent a useful tool to study this pathology. To this end, an untargeted nLC-ESI-MS/MS-based method to characterise SARS-CoV-2 proteins, including possible variants, and investigate human saliva and plasma proteome in a single analysis was developed for further application in patients. Four SARS-CoV-2 recombinant proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…To the best of our knowledge, only one study focused on the application of untargeted mass spectrometry to compare the saliva proteome of SARS-CoV-2 infected and Non-COVID individuals. Although differences in the expression of a human protein related to the defense/immunity protein, an immunoglobulin, a translational protein, and a protease inhibitor were observed, no clear link with the mechanisms of pathogenesis and response to SARS-CoV-2 could be established [32]. This is an exploratory study aimed to describe DE proteins that could be related to COVID-19 disease susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, only one study focused on the application of untargeted mass spectrometry to compare the saliva proteome of SARS-CoV-2 infected and Non-COVID individuals. Although differences in the expression of a human protein related to the defense/immunity protein, an immunoglobulin, a translational protein, and a protease inhibitor were observed, no clear link with the mechanisms of pathogenesis and response to SARS-CoV-2 could be established [32]. This is an exploratory study aimed to describe DE proteins that could be related to COVID-19 disease susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, only one study has focused on the application of untargeted mass spectrometry to compare the saliva proteome of SARS-CoV-2-infected and non-COVID-19 individuals. Although differences in the expression of a human protein related to the defense/immunity protein, an immunoglobulin, a translational protein, and a protease inhibitor were observed, no clear link with the mechanisms of pathogenesis and response to SARS-CoV-2 could be established [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not see these differences in the main comparison of groups: NcNs vs NcSus. Furthermore, as a quality control of our study, to determine the identified human proteins with the highest confidence we filtered and selected only the proteins appearing in two experiments with two internal standards, and even doing that, we obtained similar or even higher numbers compared to previous studies in nasopharyngeal swabs [ 11 ] and in saliva samples [ 32 ]). It also constitutes one of the best studies reporting the combined human proteome and microbial meta-proteome in saliva samples, since no previous study reported alterations in canonical human and microbial pathway analysis in saliva samples.…”
Section: Discussionmentioning
confidence: 99%
“…To allow safe sample manipulation, the virus was inactivated and plasma samples were digested by following the protocol described by Pagani et al [ 58 ]. Briefly, the inactivation was performed by heating samples for 60 min at 56 °C and by adding freezing ethanol (Honeywell, ≥99.8%, Offenbach, Germany), 9:1 ethanol/sample ( v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…The eluted peptides were ionised using a nanoBoosterCaptiveSpray™ (Bruker Daltonics) source using heated nitrogen dry gas (T = 150 ℃; 3 L/min) enriched with acetonitrile (ACN) (Honeywell, ≥99.9%, Offenbach, Germany). The mass spectrometer was operated in DDA (Data Dependent Acquisition Mode), with automatic switching between full-scan MS and MS/MS acquisition, as already reported [ 58 ]. N2 was used as a gas for CID (collision-induced dissociation) fragmentation.…”
Section: Methodsmentioning
confidence: 99%